A new index for measuring evenness. Issue 2 (17th January 2019) - Hussain, Zawar; Khan, Akbar Ali
ABSTRACT: Diversity and evenness play a significant role to satisfy the basic needs like food, drinking water, fuel, shelter, and medicine. Hence, these phenomena need to be measured with great precision. We propose a new index for measuring the evenness phenomenon quantitatively based on the frequencies (number of individuals) of different communities (species, families etc.). The new index is compared with fourteen other indices based on the different criteria laid down by Smith and Wilson (1996). Our proposed index, named as Z-A Index, is easy to calculate and easy to understand. Its standard limits between 0 and 1 make this new index interpretable logically. The comparison with the existing indices indicates that the newly proposed index performs well in the sense that it satisfies 11 of the 14 requirements and desirable features given by Smith and Wilson (1996).